2020
DOI: 10.1093/eurpub/ckaa040.046
|View full text |Cite
|
Sign up to set email alerts
|

Shift Work: Work ability and quality of life of professionals from IPSS

Abstract: Introduction Shift work can influence the health and well-being of individuals due to changes in biological rhythms, causing psychological and physical disruption, hampering family relationship, social and work ability. However, the shift work of auxiliary of direct / educational action of Private Social Solidarity Institution (PSSI) is essential to ensure continuity in the provision of the best hygienic and health care to the users of these institutions every day. Objectives The objective of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recent research shows that workers can be adjusted the constant changes of schedules established by their institutions, and are able to carry out their work, however, individuals with 6 or more years of work in the present-day regime shifts already feel some symptoms of physical and psychological wear, and thus speeding up their ag-ing [23]. In view of the observed results, it can be strongly concluded that the workers comprise the risk group and adequate safety, precautionary and preventive measures could only minimize exposure and the related health hazards.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research shows that workers can be adjusted the constant changes of schedules established by their institutions, and are able to carry out their work, however, individuals with 6 or more years of work in the present-day regime shifts already feel some symptoms of physical and psychological wear, and thus speeding up their ag-ing [23]. In view of the observed results, it can be strongly concluded that the workers comprise the risk group and adequate safety, precautionary and preventive measures could only minimize exposure and the related health hazards.…”
Section: Discussionmentioning
confidence: 99%